Peran Bimbingan dan Konseling dalam Mencegah dan Mengatasi Penyalahgunaan Media Sosial - Velyna, Tri (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
This study aims to analyse the role of guidance and counselling services in preventing and addressing the negative impacts of social media abuse among students. The research approach used was a descriptive qualitative approach, with data collected through in-depth interviews, participant observation, and documentation of guidance counsellors, homeroom teachers, subject teachers, and students at SMAN 2 Sangatta Utara. Data analysis was conducted using the Miles and Huberman interactive model, which includes data condensation, data presentation, and conclusion drawing. The results show that guidance and counselling services have three leading roles. First, the preventive role, realised through basic services such in providing information on digital literacy and social media ethics, as well as group guidance on social media abuse. Second, the handling role, through individual and group counselling services that help students recognise unhealthy social media usage patterns and develop adaptive coping strategies. Third, the development role, through ongoing mentoring that strengthens students' self-regulation skills and emotional intelligence, so that they can use social media wisely and responsibly. This study extends the application of self-regulation and emotional intelligence theories in the context of digital-based guidance and counseling services, emphasizing the strategic role of guidance and counseling teachers in shaping healthy social media behavior and fostering a positive digital literacy culture in the school environment.